The Effect of Changing Regular Care Provider in Type 2 Diabetes Mellitus: A Retrospective Study - Sousa Santos, Francisco (2019)
Introduction: Several studies have demonstrated the benefits of having a regular care provider on the control of chronic diseases. Our study intends to clarify the effects of the transition to a new diabetologist on metabolic control in type 2 diabetes patients followed-upin a tertiary care setting.Material and Methods: Retrospective study performed in an endocrinology outpatient clinic. We randomly selected 50 type 2 diabetespatients for a control group and 50 for a study group. In the study group, we registered the last evaluation before the physician change (year 0) and at the end of each year (year 1, 2 and 3) with the new doctor. Evaluated variables — body mass index, blood pressure, HbA1c and lipid profile — were compared yearly between groups.Results: There was a decrease in mean HbA1c levels (0.4% – 0.5%, p < 0.05) in year 1 and 2 when compared to year 0 in the study group, but not in the control group. This reduction was superior (0.5% – 1.4%, p < 0.05) in patients whose baseline HbA1c was greater than 7%. The other studied variables did not vary significantly throughout follow-up in either group.Discussion: In our study the transition to a different type 2 diabetes physician was associated with a decrease in mean HbA1c and this difference was greater in less well controlled patients.Conclusion: Switching to a new physician may not be harmful and may actually have benefits for the glycemic control of some type 2 diabetes patients.